1991
DOI: 10.1128/jb.173.20.6364-6372.1991
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of a novel protease gene encoding an extracellular neutral protease from Bacillus subtilis

Abstract: We have cloned from Bacillus subtilis a novel protease gene (nprB) encoding a neutral protease by using a shotgun cloning approach. The gene product was determined to have a molecular mass of 60 kDa. It has a typical signal peptide-like sequence at the N-terminal region. The expression of nprB can be stimulated by using a B. subtilis strain, WB30, carrying a sacUh mutation. Expression of this protease gene results in production of a 37-kDa protease in the culture medium. The first five amino acid residues from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…This, therefore, strongly suggests that a DNA rearrangement occurred downstream of the dap operon, giving rise to the difference between strain 168 and strain GS11. Finally, it is important to note that nprB was, in fact, previously mapped at 95" (Tran et al, 1991), whilst the location of ipi on the chromosome was not reported earlier.…”
mentioning
confidence: 99%
“…This, therefore, strongly suggests that a DNA rearrangement occurred downstream of the dap operon, giving rise to the difference between strain 168 and strain GS11. Finally, it is important to note that nprB was, in fact, previously mapped at 95" (Tran et al, 1991), whilst the location of ipi on the chromosome was not reported earlier.…”
mentioning
confidence: 99%
“…Two major extracellular proteases are produced during the onset of sporulation, the alkaline serine protease subtilisin (AprE) (18,38) and a neutral protease (NprE) (40). The minor extracellular proteases include Epr (2,27), bacillopeptidase F (Bpr) (30,31,39), metalloprotease (Mpr) (20,23,28), neutral protease B (NprB) (35), wall-associated extracellular protease (WprA) (17), and Vpr (29). Expression of these proteolytic enzymes seems to be tightly regulated (33), and their major function is thought to be supplying amino acids for growth via degradation of extracellular proteins.…”
mentioning
confidence: 99%
“…Furthermore, we show that existing differences in specificity and activity between two individual members can be canceled by a single amino acid substitution. (25), the nprT gene encoding the TLP of Bacillus stearothermophilus CU21 (26) (TLP-ste), the nprC gene encoding the TLP of Bacillus cereus (3)(TLP-cer), and the nprB gene encoding the TLP-sub of Bacillus subtilis (27) were cloned, subcloned, and expressed as described previously (28). The purified TLP-sau of Staphylococcus aureus (29) (aureolysin, EC 3.4.24.29) was kindly provided by Dr. J. Potempa.…”
mentioning
confidence: 99%